Pemasangan Lampu Penerangan Jalan Umum untuk Meningkatkan Keamanan dan Aktivitas Malam Hari Masyarakat Desa Cangkring - Safrizal Safrizal; Syukriyadin Syukriyadin; Alfisyahrin Alfisyahrin (Indo Publishing, 2025)
Limited street lighting at night is one of the problems faced by the community of Cangkring Village, Karanganyar District, Demak Regency. Insufficient public street lighting results in dark road conditions, which may reduce environmental safety, increase the risk of traffic accidents, and limit community activities during nighttime. Adequate public street lighting is therefore essential to support safety, comfort, and community mobility.This community service activity aimed to improve environmental security and support nighttime community activities through the installation of public street lighting (PJU) in Cangkring Village. The implementation method was carried out in several stages, including a pre-implementation stage consisting of site surveys and coordination with village authorities to identify priority locations. The implementation stage involved installing public street lights at designated points, followed by an evaluation stage through functional testing of the installed lamps and collecting feedback from the community.The results showed that all installed public street lights functioned properly during testing. Roads that previously lacked sufficient lighting became adequately illuminated, improving nighttime visibility. Community feedback indicated an increased sense of safety and comfort when traveling and conducting activities at night. Based on these measurable results, the community service program can be considered successful in addressing the issue of limited street lighting. This activity is expected to contribute to improving basic village infrastructure and serve as a reference for similar community service programs in rural areas.